2016
DOI: 10.14336/ad.2015.1009
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Oxidative Stress in Ischemic Stroke

Abstract: The prevalence and incidence of stroke rises with life expectancy. However, except for the use of recombinant tissue-type plasminogen activator, the translation of new therapies for acute stroke from animal models into humans has been relatively unsuccessful. Oxidative DNA and protein damage following stroke is typically associated with cell death. Cause-effect relationships between reactive oxygen species and epigenetic modifications have been established in aging, cancer, acute pancreatitis, and fatty liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 140 publications
(112 reference statements)
1
85
0
Order By: Relevance
“…In the working skeletal muscle, NOX2‐dependent ROS generation has been reported to lead to nuclear efflux of HDAC4 and HDAC5 and muscle remodelling (Liu et al , ). Similarly, ROS increased nuclear exit of HDAC4/5 in angiotensin‐II‐induced vascular remodelling and cerebral ischaemic injury (Wang et al , ; Zhao et al , ) (Figure ).…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 83%
See 3 more Smart Citations
“…In the working skeletal muscle, NOX2‐dependent ROS generation has been reported to lead to nuclear efflux of HDAC4 and HDAC5 and muscle remodelling (Liu et al , ). Similarly, ROS increased nuclear exit of HDAC4/5 in angiotensin‐II‐induced vascular remodelling and cerebral ischaemic injury (Wang et al , ; Zhao et al , ) (Figure ).…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 83%
“…For example, hypermethylation of the gene encoding the transcription factor KLF4 decreased the expression of endothelial NOS under these conditions (Dunn et al , ). While these studies suggest that ROS can induce specific hypermethylation by up‐regulating DNMTs, several studies found that ROS can also affect DNA methylation by modulating the DNA recruitment of DNMTs without affecting DNMT expression (Lim et al , ; Zhao et al , ). For example, ROS induced Snail, which was required to recruit DNMT1 to the E‐cadherin promoter for hypermethylation (Lim et al , ).…”
Section: Effects Of Reactive Oxygen Species On Epigenetic Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…5hmC, which is produced from the oxidation of 5mC by Tet enzymes (Ko et al, ; Tahiliani et al, ), exists in genomic DNA (Penn, Suwalski, O'Riley, Bojanowski, & Yura, ), RNA (Huber et al, ), and mitochondrial DNA (mtDNA) (Shock, Thakkar, Peterson, Moran, & Taylor, ). Epigenetic modifications are emerging as an important mechanism for neuronal survival versus death after ischemic brain injury (Jhelum, Karisetty, Kumar, & Chakravarty, ; Zhao, Han, Ji, & Luo, ). Previous studies with colorectal cancer cells have shown that mtDNA methylation directly influences the mtDNA copy number and further alters the cell cycle, apoptosis, and proliferation (Tong et al, 2017).…”
Section: Introductionmentioning
confidence: 99%